2018
DOI: 10.1523/eneuro.0251-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neural Pattern Classification Tracks Transfer-Appropriate Processing in Episodic Memory

Abstract: The transfer-appropriate processing (TAP) account holds that episodic memory depends on the overlap between encoding and retrieval processing. In the current study, we employed multivariate pattern analysis (MVPA) of electroencephalography to examine the relevance of spontaneously engaged visual processing during encoding for later retrieval. Human participants encoded word-picture associations, where the picture could be a famous face, a landmark, or an object. At test, we manipulated the retrieval demands by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The greater the cue overlap — similarity between the neural representations of the cue and the stored information — the more likely the information is to be retrieved (but see Nairne, 2002 ). For example, it is well established that reinstating the original context in which information was studied, such as a location, benefits memory (see Smith & Vela, 2001 for review), particularly when task demands require retrieval of context (Bramão & Johansson, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The greater the cue overlap — similarity between the neural representations of the cue and the stored information — the more likely the information is to be retrieved (but see Nairne, 2002 ). For example, it is well established that reinstating the original context in which information was studied, such as a location, benefits memory (see Smith & Vela, 2001 for review), particularly when task demands require retrieval of context (Bramão & Johansson, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brain oscillatory activity has been previously used to successfully train pattern classifiers to distinguish mnemonic representations ( Jafarpour et al. 2014 ; Bramão and Johansson 2018 ) and is thought to support core mechanisms of episodic memory ( Hanslmayr and Staudigl 2014 ; Hanslmayr et al. 2016 ; Schreiner and Staudigl 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…More direct neural evidence for internal reinstatement comes from both fMRI and EEG studies that have shown reactivation of neural patterns from targeted studied events. Goal-related neural activity has been detected prior to cued retrieval attempts in several studies, but does not directly show proactive reinstatement of study neural patterns before retrieval unfolds (Bramão et al, 2022;Bramão & Johansson, 2018;Manning et al, 2011;McDuff et al, 2009). This evidence is complemented by findings that study phase neural patterns reappear in the first second or so of memory search in free recall tasks, although such patterns are difficult to distinguish from those accompanying initial recollection (Kragel et al, 2021;Polyn, 2005;Polyn et al, 2012; see also Bramão et al, 2022;Bramão & Johansson, 2018).…”
Section: Introductionmentioning
confidence: 98%